#TITLE_ALTERNATIVE# - TRI HANINDRIYO (NIM : 13311050); YUSUF YUDA PRAWIRA (NIM : 13311075); Pembimbing : Prof. Ir. H, ADIE
Direct Hydrazine Fuel Cell (DHFC) is a promising alternative energy source. Transition metals can replace the rare platinum as catalyst. Both the mixture of Ni-Co and Ni-Zn transition metals as DHFC catalyst produces larger power density than pure nickel catalyst. Density Functional Theory was used in the computational design of a Ni-Co and Ni-Zn catalyst by modelling the adsorption of hydrazine molecules on Ni-Co and Ni-Zn surface (111), using structure variation in the form of Co and Zn atom concentration on the topmost surface layer. The active sites were the Ni and Co/Zn top sites. Hydrazine adsorption on the Ni-Co surface for every structural and active site variations produced a lower adsorption energy than on a pure nickel surface. Hydrazine adsorption on Ni top sites produced higher adsorption energy than on Co/Zn top sites. Substitution of Ni atoms with Zn atoms on nickel surface reduces/eliminates the magnetic property of the surface. For several systems, hydrazine adsorption changed the conformation of the hydrazine molecule from anti to gauche. This conformation change is probably related to the increase of adsorption energy. Only one system, in which Zn concentration on topmost surface layer is 25% and the active site is the Ni top site, produced a higher adsoprtion energy than a pure nickel surface.